Premature closure of the caudal calvarial midline suture is associated with scaphocephaly and ventriculomegaly in Boxer dogs - Farke, Daniela; Guillier, Blanche; Büttner, Kathrin; Schmidt, Martin J. (Frontiers in Veterinary Science, 2026)
IntroductionBoxer dogs exhibit a distinctive skull morphology resembling scaphocephaly in humans. This study investigates the status of skull sutures in Boxer dogs in comparison with other brachycephalic and mesocephalic breeds.MethodsArchival magnetic resonance images of the heads of 312 dogs with variable skull morphologies were examined. Sutures and synchondroses of the skulls were assessed as open or closed, and the presence or absence of ventricular dilation was noted.ResultsA total of 160 dogs belonged to the mesocephalic group, 103 were brachycephalic, and 49 were Boxer dogs. Age was a predictor for closed sutures and synchondroses (p < 0.05). Sutures and synchondroses were more likely closed in brachycephalic compared to mesocephalic dogs (p < 0.0001). In addition, brachy- and mesocephalic dogs were less likely to show a closed sagittal suture (S4), parietointerparietal suture (S9) (p < 0.0001), and lambdoid sutures (p < 0.05) than Boxer dogs. Cranial index was higher in brachycephalic dogs compared to mesocephalic dogs and Boxer dogs and significantly differed among all groups (p < 0.05). Width/height index of the skull was significantly different among all groups and lowest in Boxer group (p < 0.05). Boxer dogs more likely experienced ventriculomegaly than the other breeds (p < 0.0001).Discussion/conclusionThe parietointerparietal and sagittal suture are more likely fused in Boxer dogs. A premature suture closure is most likely responsible for the Boxer dog’s unique skull morphology or scaphocephaly and an associated ventriculomegaly, which resembles a non-syndromical craniosynostosis in humans.